Analisis Kinerja Perlintasan Sebidang Rel Kereta Api Jalan Jagalan Mranggen (Indonesian Journal of Civil Engineering Study, 2025)
Mranggen District is a densely populated region inside Demak Regency, notable for its C-type mining resources.  The high population density and industrial zone contribute to elevated traffic volume.  Observations indicate that the road segment near the Jagalan Road level crossing suffers from congestion, extended waits, and significant delays.  An investigation is required to assess the performance and service level at the Jagalan Road level crossing based on these data.  The performance evaluation of the level crossing was conducted using the Indonesian Road Capacity Guidelines (PKJI) 2023 methodology, in accordance with the stipulations outlined in the regulation of the Director General of Land Transportation Number 770 of 2005.  The study findings indicated that the maximum traffic flow at the level crossing was recorded on Saturday, February 23, 2025, reaching 1014.9 pcu/hour, against a road capacity of 3360 pcu/hour, yielding a saturation degree of 0.30 and a service level of B.  In the assessment of level crossing requirements and the identification of level crossings, the Jagalan Road crossing may be upgraded to a grade-separated crossing.